Biogas from Organic Waste Diluted with Sugar Mill Waste Water - GOEL, ANJALI; GUPTA, SAVITA (Asian Journal of Chemistry, 2010)
The biogas production depends on various factors, such as charactersitcs of feed components, ratio of blending of feed components, type of water used, pH and temperature, etc. In the present studies, rice straw and cow dung are used as feed components. The gas production was recorded weekly. It has been observed that with the increase of rice straw blending, the rate of gas production increases. In the next series of experiments, the gas production blended with cow dung, rice straw and distilled water/sugar mill eflluent has been carried out. It is observed that digesters blended with distilled water show minimum gas production as compared to others with Deoband, Khatauli or Uttam sugar mill effluent. The characteristics like total solids, volatile solids, carbon, nitrogen, C/N ratio and protein contents of feed component have been studied initially and after 4 weeks. The results show a decrease in the values of all the characteristics. The effect of pH has also been studied in the pH ranges of 5 to 9. The results indicate that for biogas production pH-7 is most suitable. The amount of CO2 produced in biogas was estimated volumetrically.